Lärares språkbruk i tvåspråkiga klassrum - Avery, Helen (Educare, 2011)
The article presents results of a study made in the context of introducing bilingual instruction in Swedish and Arabic. Classroom interaction was videotaped in grades one to four at two urban schools. Based on the video material, an inventory was made of how Arabic was used by the bilingual teachers, and how it related to the corresponding Swedish content. Simplified language use, code-switching and relations between use of Arabic and Swedish were analysed with respect to potential impact on learning affordances. Results indicate that, despite the introduction of bilingual instruction, Swedish still appeared as the dominant school language. Subject matter was frequently introduced in Swedish and then translated into Arabic. Considering that the schoolchildren were bilingual, many of the translations became repetitive rather than explanatory. Arabic syntax in teacher presentations was simplified. Frequent codeswitching within utterances further contributed to simplifying both syntax and content. In other instances, however, open questions and relating written forms to their own expressions developed the pupils’ skills in Arabic. Involving the pupils’ personal experience increased engagement and motivation.